IMPROVING STUDENTS’ SPEAKING SKILL THROUGH RETELLING TECHNIQUE BY USING YOUTUBE VIDEO - Fadilaturrahmah Fadilah (Jurnal Pendidikan Pemuda Nusantara, 2022)
The aim of this study was to find out whether or not there was any significant difference speaking skills between students’ who were taught through retelling technique by using YouTube videos and those who were not at tenth graders of SMK Muhammadiyah Pagar Alam. The population of this research was 370 students which divided in to eleventh classes at tenth graders of SMK Muhammadiyah Pagar Alam. The sample was taken from 35 students of OTKP 1 and 35 students from OTKP 2 by using purposive sampling. This research used Quasi-experimental design as the research design. The data was taken from oral test which used 2 raters, and the data was analyzed by using SPSS. The result of this study was revealed that there was significant difference between students who were taught through retelling technique by using YouTube videos and those who were not at tenth graders of SMK Muhammadiyah Pagar Alam. It proves that the use of YouTube videos (narrative story) and retelling technique as strategy to support the main action was effective and could improve students speaking skills.